Microsoft Windows 7 on demand - Johnson, Steve, 1961- (On demand (Indianapolis, Ind.), 2009)
Need answers quickly? Microsoft Windows 7 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Inside the Book · Master the Windows 7 user experience, including Windows Aero · Perform Instant Searches to quickly find files and programs · Manage files and information using Windows 7 programs and desktop gadgets · Browse the Web, search for information, and get instant updates · Use Windows Live Essentials to work with mail, messages, photos, and movies · Protect your computer from Internet or network intruders · Create your own movies, slide shows, and DVDs · Rip, manage, and play digital music and videos · Share files and media on a HomeGroup or network · Set multiple users and parental controls · Customize, fine-tune, and administer Windows 7 Bonus Online Content Register your book at queondemand.com to gain access to: Workshops and related files Keyboard shortcuts.